PENGARUH METODE PEMBELAJARAN EKSPERIMEN TERHADAP KETERAMPILAN SAINS ANAK DI TK TUNAS CAHAYA - Sri Dewi; Marmawi R; Annisa Amalia (Universitas Tanjungpura, 2022)
AbstractThis research aims to find out the influence of experimental learning methods on children’s science skills in TK Tunas Cahaya. The research method used is quantitative with quasi experimental design approach with the from nonequivalent control group design. The study sample included all children in TK Tunas Cahaya with a total of 12 childern. Research instruments are using observation sheets and checklists. Data collection tools use observation techniques and documentation technique. Based on the results of the analysis showed a difference in final results ehere the experimental class with a score of 90 compared to the control class with a score of 74. The Wilcoxon match pairs test calculation using SPSS for windows version 23 shows a Z value of - 2,214 and Asymp. Sig (2 tailed) of 0.027 with calculation conditions ˃ so accepted. Because ˂ that is 0.027 ˂ 0.05 then rejected and accepted. So, it can be conclude that there is an influence of experimental learning methods on children’s science skill in TK Tunas Cahaya.Keywords: Experimental Learning Methods, Science Skills